Climate-sensitive health counselling in Germany: a cross-sectional study about previous participation and preferences in the general public - Krippl, Nicola; Mezger, Nikolaus Christian Simon; Danquah, Ina; Nieder, Jessica; Griesel, Silvan; Schildmann, Jan; Mikolajczyk, Rafael; Kantelhardt, Eva Johanna; Herrmann, Alina (BMC public health, 2024)
Background: In response to climate change (CC), medicine needs to consider new aspects in health counselling of patients. Such climate-sensitive health counselling (CSHC) may include counselling patients on preventing and coping with climate-sensitive diseases or on leading healthy and climate-friendly lifestyles. This study aimed to identify previous participation in and preferences for CSHC as well as associated sociodemographic and attitudinal factors among the general public in Germany. Methods: We conducted a cross-sectional study in a population-based online panel in five German federal states (04–06/2022). We performed descriptive statistics and multivariable regression analysis to assess prior participation in CSHC and content preferences regarding CSHC, as well as associations between sociodemographic variables and general preference for CSHC. Results: Among 1491 participants (response rate 47.1%), 8.7% explicitly reported having participated in CSHC, while 39.9% had discussed at least one CSHC-related topic with physicians. In the studied sample, 46.7% of participants would like CSHC to be part of the consultation with their physician, while 33.9% rejected this idea. Participants aged 21 to 40 years (versus 51 to 60), individuals alarmed about CC (versus concerned/cautious/disengaged/doubtful/dismissive), and those politically oriented to the left (vs. centre or right) showed greater preference for CSHC in the multivariable regression model. Most participants wanted to talk about links to their personal health (65.1%) as opposed to links to the health of all people (33.2%). Conclusions: Almost half of the participants in this sample would like to receive CSHC, especially those who are younger, more alarmed about CC and more politically oriented to the left. More research and training on patient-centred implementation of CSHC is needed.